In Vitro and In Silico Antidiabetic Efficacy of Solanum lasiocarpum Dunal Fruit Extract. - Jing Zhao; Ahmed Abdulkareem Najm; Ibrahim Mahmood; Zhang Yu Ming; Partha Pratim Dutta; Wamidh H Talib; Douglas Law; Shazrul Fazry (PLoS ONE)
Exploring the possibility of familiar dietary sources as additional diabetes treatments is crucial, especially considering the financial difficulties related to diabetes mellitus. Using both in vitro and in silico techniques, this work aims to assess the antidiabetic benefits of extract from Solanum lasiocarpum Dunal. The evaluations encompass the ability to scavenge DPPH radicals, inhibition of α-amylase, α-glucosidase, inhibition of DPP-4, cytotoxicity, and glucose absorption kinetics. With an IC50 value of 0.69 ±  0.14 mg/ml, S. lasiocarpum showed encouraging DPPH inhibition. IC50 values of 2.123 ±  0.14 mg/ml inhibited the enzymes α-amylase, α-glucosidase, and DPP-4. Furthermore, a notable increase (P < 0.05) in glucose uptake by L6 myoblasts was observed with the administration of various combinations. In silico analysis, including XP docking and MM-GBSA, revealed that 10 and 21 compounds within the combination exhibited substantial interactions and stable binding capabilities with α-amylase and DPP-4 proteins, indicating their potential as enzyme inhibitors. Therefore, it can be inferred that S. lasiocarpum represents a promising therapeutic approach for diabetes management.